Analisis Kualitas Lingkungan dan Dampaknya Terhadap Masyarakat di Sekitar TPA Sukawinatan Palembang - Rahayona, Detrilice; Sunarsih, Elvi; Egit, Khaifagita Fitriand; Azzarah, Nurahma Dania; Rahmah, Silvi Aulia; Kartika, Tarisa Putri (Public Health Department, Universitas Islam Negeri Alauddin Makassar, 2023)
TPA Sukawinatan is one of the final disposal sites that is still operating actively in Palembang City. Garbage is often a risk for a city to become a megalopolis. With a large population and high growth rate, the amount of waste is increasing. Many cities in Indonesia have built Final Processing Sites (TPA) without regard to TPA production standards and without regard to Environmental Impact Analysis (AMDAL). The purpose of this study to identify the waste management system and community participation in Sukajaya Village, Sukarami District. Using cross-sectional, descriptive, observational research methods. With the population of abiotic components and samples of the surrounding community. Garbage produced by the Sukawinatan community is disposed of in a landfill, causing a pungent odor throughout the day. Environmental pollution due to waste has recently increased rapidly. On that basis, this study aims to determine whether the waste management at Sukawinatan TPA complies with the applicable budget based on Regional Regulation 7 of 2016. Environmental pollution in the Sukawinatan TPA area, especially in the air and soil, greatly impacts the health of the community resulting in a decrease in the level of public health. The active role of the community is also needed to live a clean and healthy life by applying the 4R principles and improving technology in waste management according to the type of waste. Keywords : TPA, Waste Management, TPA Sukawinatan